Analisis Minat Menabung Mahasiswa Generasi Z Ditinjau dari Gaya Hidup, Kontrol Diri, dan Perilaku Keuangan - Hildegardis Goba Mboti; Andri Paulus Loe; Fernando Saragih (CV. Global Cendekia Inti, 2026)
Saving interest is an important aspect influenced by financial behavior, lifestyle, and self-control. Therefore, this study focuses on the characteristics of Generation Z as a group with distinctive financial behavior patterns. This study aims to analyze the influence of lifestyle and self-control on Generation Z students’ saving interest through financial behavior as a mediating variable. This study employs the Theory of Planned Behavior (TPB) as the theoretical framework to explain how personal and social factors can influence students’ saving interest through the formation of financial behavior. This study uses a quantitative approach with a survey method involving 100 students from five public universities in Kupang City selected through incidental sampling. The data were analyzed using path analysis. The results indicate that lifestyle and financial behavior have a positive and significant effect on saving interest, whereas self-control does not have a significant direct effect but has an indirect effect through financial behavior. These findings indicate that financial behavior plays an important role as a mediator in increasing students’ saving interest. This study contributes to expanding the application of the Theory of Planned Behavior in explaining the saving behavior of Generation Z students in the digital transaction era.